Die „Ichitarô“-Entscheidung des Obergerichtes für geistiges Eigentum (2005 (Ne) 10040) - Beyerlein, Thorsten (Zeitschrift für Japanisches Recht, 2007)
The Intellectual Property High Court of Tokyo has ruled in its first decision ever on indirect patent infringement. The alleged infringement of a so-called software patent was of high interest to the public due to the involvement of the well-known Japanese word-processing software Ichitarô and the graphic software Hanako. The Intellectual Property High Court finally ruled that though an indirect infringement of the product claims of the software patent had taken place, this software patent could not be enforced due to the lack of an inventive step. An indirect infringement of the process claim has been completely denied.